2020
DOI: 10.1074/jbc.ra120.014905
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal small-molecule screening for human prion protein binders

Abstract: Prion disease is a rapidly progressive neurodegenerative disorder caused by misfolding and aggregation of the prion protein (PrP), and there are currently no therapeutic options. PrP ligands could theoretically antagonize prion formation by protecting the native protein from misfolding or by targeting it for degradation, but no validated small-molecule binders have been discovered to date. We deployed a variety of screening methods in an effort to discover binders of PrP, including 19F-observed and saturation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 91 publications
2
13
0
Order By: Relevance
“…On the other hand, the four small chemical compounds described to bind PrP and tested here, did not induce increased release. The latter may fit a recent report suggesting that PrP is a difficult-to-target protein, at least with small ligands, and implying that, for PrP ligands to be therapeutically effective, they have to have a certain size and binding characteristics [130]. This, in turn, reinforces the use of nonsmall-molecules, such as antibodies or their derived smaller fragments, which is currently pursued despite obvious difficulties in administration and pharmacokinetics [74].…”
Section: Discussionsupporting
confidence: 62%
“…On the other hand, the four small chemical compounds described to bind PrP and tested here, did not induce increased release. The latter may fit a recent report suggesting that PrP is a difficult-to-target protein, at least with small ligands, and implying that, for PrP ligands to be therapeutically effective, they have to have a certain size and binding characteristics [130]. This, in turn, reinforces the use of nonsmall-molecules, such as antibodies or their derived smaller fragments, which is currently pursued despite obvious difficulties in administration and pharmacokinetics [74].…”
Section: Discussionsupporting
confidence: 62%
“…To investigate whether G418 or puromycin might interact directly with PrP C , we generated recombinant MoPrP (recPrP) and performed differential scanning fluorimetry, a technique capable of detecting shifts in PrP thermal stability upon binding of small molecules ( 50 , 51 ). In the presence of a tenfold molar excess of either puromycin, G418, or quinacrine, a ratio commonly used in protein thermal shift experiments ( 52 ), the melting temperature of recPrP remained unchanged, suggesting that none of these compounds likely act by binding to PrP C and modulating its stability ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds were assessed for PARP10 inhibition, and they found two compounds with promising results [195]. In another study, Reidenbach et al attempted to identify compounds against Prion disease, a neurodegenerative disease with no therapeutic options; however, the only benzimidazole compounds identified demonstrated low affinities [196]. Whereas, Cuozzo et al screened a DECL library of 225 million compounds, and identified a single compound (X-165) with a high activity against the production of lysophosphatidic acid, and this compound has been approved by the FDA for Phase I Clinical trials [197].…”
Section: Compound Screeningmentioning
confidence: 99%